Polycyclic Aromatic Hydrocarbons Affect Rheumatoid Arthritis Pathogenesis via Aryl Hydrocarbon Receptor - Xi, Xiaoyu; Ye, Qinbin; Fan, Danping; Cao, Xiaoxue; Wang, Qiong; Wang, Xing; Zhang, Mengxiao; Xu, Yuan; Xiao, Cheng (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA), the most common autoimmune disease, is characterized by symmetrical, synovial inflammation of multiple joints with the infiltration of proinflammatory immune cells and increased cytokine (CK) levels. In the past few years, numerous studies have indicated that a number of factors affect RA, such as mutations in susceptibility genes, epigenetic modifications, age, and race. Recently, environmental factors, especially polycyclic aromatic hydrocarbons (PAHs), have attracted increasing attention for their role in RA pathogenesis. Therefore, it is particularly important to explore the specific mechanisms of PAHs in RA. In this review, we summarize the recent progress in understanding the mechanisms of PAHs and aromatic hydrocarbon receptors (AHRs) in RA. In addition, the development of therapeutic drugs that target AHR is also reviewed. Finally, we discuss the challenges to and perspectives on PAH application in the future.